Lumiere park café : Almere, Holanda. 1999- - SANAA Ltd. (2004)
El programa combina un café con talleres para dos artistas en el parque Lumiere de <Almere>.
Keywords: NISHIZAWA, RY¯UE; SEJIMA, KAZUYO; PAISES BAJOS; ARQUITECTURA COMERCIAL; BARES; TALLERES; PROYECTOS